2017
DOI: 10.3389/fneur.2017.00648
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Imaging Characteristics and Its Clinical Relevance in Patients with Cerebral Venous Thrombosis—A Retrospective Analysis from One Single Center in China

Abstract: BackgroundFew studies have investigated structural imaging findings of cerebral venous thrombosis (CVT) in China. The structural imaging [head computed tomography (CT) and routine brain magnetic resonance imaging (MRI)] can assess any parenchymal lesion secondary to the venous thrombosis and reveal direct signs of intraluminal thrombus. In recent years, many patients can be diagnosed with CVT more rapidly and directly by structural imaging. The aim of the present study is to determine the performance of struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
1
6
2
2
Order By: Relevance
“…In addition, neuroimaging findings indicated that the most common sinus affected was sigmoid sinus, the most common number of sinus involvement was "more than two", without difference between two groups. Our results might be inconsistent with other studies, because the proportion of sinus involvement was quite variable due to the type and timing of neuroimaging (Devasagayam et al, 2016;Kalita et al, 2016;Wang et al, 2019;Zhou et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, neuroimaging findings indicated that the most common sinus affected was sigmoid sinus, the most common number of sinus involvement was "more than two", without difference between two groups. Our results might be inconsistent with other studies, because the proportion of sinus involvement was quite variable due to the type and timing of neuroimaging (Devasagayam et al, 2016;Kalita et al, 2016;Wang et al, 2019;Zhou et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…(1) Edema can be detected on CT or MR images by observing focal irregularities in attenuation or signal intensity. These abnormalities can be further categorized into two types: vasogenic edema, characterized by elevated ADC values that are presumed to be associated with venous congestion, and cytotoxic edema, characterized by reduced ADC values attributed to cellular energy disruption, as revealed by DWI techniques [ 13 ]. (2) Venous infarction is defined as the presence of brain parenchymal lesions that encompass local edema as well as petechial or confluent cerebral hemorrhage [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral infectious thrombophlebitis is rare. However, women of childbearing age are at high risk, and about 58.1% of infectious thrombophlebitis occurs in this age group (28). Cerebral venous thrombosis (CVT) accounts for nearly all intracranial thrombosis with incidence 0.5-1.0%, but the incidence increases to as high as 5% of all strokes in the younger population (29,30).…”
Section: Venous Cerebrovascular Complications Of Infectionsmentioning
confidence: 99%